Analisis Faktor Produksi Dan Pendapatan Usaha Perikanan Tangkap Nelayan Di Kelurahan Bantaya Kecamatan Parigi Kabupaten Parigi Moutong - Hi. Sahido, Listiawati HI.S.AL. (Mitra Sains, 2016)
The aims of this research are: (1) analyzing the supplies effect, the effective working days, the catching trip, the fishing equipment which affecting the fishermen result in catching fish of Bantaya Village, Parigi Sub-District in Parigi Moutong Regency, (2) Analyzing the fishermen income in bantaya Village Parigi Sub-District in Parigi Moutong Regency. The sample of this research is fishermen in Bantaya village, and then the method used was census method. The instruments of data collection were observation and interview which analyzed through multiple linear regression and income analysis. The result of the research by using multiple linear regression showed that coeffcient of determination (R2) is 0.849. Going through Ftest, it shows that Fcounted = 80.034 > Ftable = 3.695 on α = 1%, it proves that Null hypothesis was rejected. It means that the independent variable (1n X1), labor (1n x2), the number of catching trip (1n X3) the fishing equipment (D) simultaneously affects the result of catching fish in bantaya Village Parigi Sub-District in Parigi Moutong Regency. Furthermore, the fisheries’ income in Kelurahan of Bantaya with the production cost is Rp. 26.208.658,-/ month, which consists of fixed amount is Rp. 16.101.847,-/month and the variable cost is Rp. 10.106.810,-/month, the amount income is Rp. 53.881.207,-/month, so that the amount before sharing profit is Rp. 27.672.549,-/month, while income after sharing profit is Rp. 3.231.213,-/month.